Probable Animal-to-Human Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Delta Variant AY.127 Causing a Pet Shop-Related Coronavirus Disease 2019 (COVID-19) Outbreak in Hong Kong. (2nd March 2022) - Chan, Jasper Fuk Woo; Siu, Gilman Kit Hang; Yuan, Shuofeng; Ip, Jonathan Daniel; Cai, Jian Piao; Chu, Allen Wing Ho; Chan, Wan Mui; Abdullah, Syed Muhammad Umer; Luo, Cuiting; Chan, Brian Pui Chun; Yuen, Terrence Tsz Tai; Chen, Lin Lei; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can infect human and other mammals, including hamsters. Syrian ( Mesocricetus auratus ) and dwarf ( Phodopus sp.) hamsters are susceptible to SARS-CoV-2 infection in the laboratory setting. However, pet shop-related Coronavirus Disease 2019 (COVID-19) outbreaks have not been reported. Methods: We conducted an investigation of a pet shop-related COVID-19 outbreak due to Delta variant AY.127 involving at least 3 patients in Hong Kong. We tested samples collected from the patients, environment, and hamsters linked to this outbreak and performed whole genome sequencing analysis of the reverse transcription polymerase chain reaction (RT-PCR)-positive samples. Results: The patients included a pet shop keeper (Patient 1), a female customer of the pet shop (Patient 2), and the husband of Patient 2 (Patient 3). Investigation showed that 17.2% (5/29) and 25.5% (13/51) environmental specimens collected from the pet shop and its related warehouse, respectively, tested positive for SARS-CoV-2 RNA by RT-PCR. Among euthanized hamsters randomly collected from the storehouse, 3% (3/100) tested positive for SARS-CoV-2 RNA by RT-PCR and seropositive for anti-SARS-CoV-2 antibody by enzyme immunoassay. Whole genome analysis showed that although all genomes from the outbreak belonged to the Delta variant AY.127, there were at least 3 nucleotide differences among the genomes from different patients and the hamster cages. Genomic analysis suggests that multiple strains have emerged within the hamster population, and these different strains have likely transmitted to human either via direct contact or via the environment. Conclusions: Our study demonstrated probable hamster-to-human transmission of SARS-CoV-2. As pet trading is common around the world, this can represent a route of international spread of this pandemic virus. Abstract : We report a SARS-CoV-2 Delta variant AY.127 outbreak related to a pet store in Hong Kong. Genomic analysis showed that multiple strains were involved. Our study highlighted the possibility of SARS-CoV-2 being transmitted from hamsters to human in the community.